Dexamethasone sodium phosphate intercalated layered double hydroxides and their therapeutic efficacy in a murine asthma model1. Issue 30 (3rd April 2015) - Wang, Wen-Rui; Li, Ang; Mei, Wei; Zhu, Rong-Rong; Li, Kun; Sun, Xiao-Yu; Qian, Ye-Chang; Wang, Shi-Long
<x xml:space="preserve">Abstract</x> Schematic diagram showing the intercalation of Dexa into the MgAl–LDH interlayers.